Evaluation of a diesel engine performance and emission using biogas in dual fuel mode - Das, Amar Kumar; Padhi, Manas Ranjan; Behera, Debashree Debadatta; Das, Shiv Sankar (Mechanical Engineering for Society and Industry, 2024)
Environmental pollution and the gradual depletion of fossil fuels have recently shifted the focus to alternate fuels. Hence, more diversified research on alternate fuels is necessary to deal with the global energy crisis. Biogas extracted from biomass is an excellent alternative to fossil fuels due to its low cost and good mixing ability. It is mainly generated by anaerobic digestion of organic waste products in a digester tank. The present paper investigates the performance and emission characteristics of diesel engine in dual fuel mode with biogas as main fuel and diesel as pilot fuel without any engine modification. The main aspect of the paper is to critically study the effect of supplementation of biogas on diesel engine efficiency and emission level of important constituent gases such as CO2 and NOX. Our findings demonstrate that the essential performance result of engine, such as Brake Thermal Efficiency (BTE) and Mechanical Efficiency for the biogas-air mixture of 20% (DB20), was slightly decreased. At the same time, there was a reduction in brake-specific fuel consumption (BSFC) compared to pure diesel. Furthermore, the exhaust emission of NOX and CO2 was lowered when the engine was operated in dual fuel induction mode. The results of engine performance were found to be better than the results of other researchers for engines of same specifications and operating conditions. Hence, biogas serves as a viable alternative fuel and contributes to cleaner combustion, offering a promising solution for reducing the environmental impact of diesel engines. The study provides critical insights into optimizing dual fuel systems for enhanced performance and sustainability.